1983
DOI: 10.3758/bf03205861
|View full text |Cite
|
Sign up to set email alerts
|

Color segregation and selective attention in a nonsearch task

Abstract: Relations between selective attention and perceptual segregation by color were investigated in binary-choice reaction time experiments based on the nonsearch paradigm of Eriksen and Eriksen (1974). In focused attention conditions (Experiment 1), noise letters flanking a central target letter caused less interference when they differed from the target in color, although color carried no information as to whether or not a letter was the target. When blocking of trials favored a strategy of dividing attention bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
122
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 45 publications
11
122
1
Order By: Relevance
“…They demonstrated that the interference created by a distracting item on the processing of a target was increased if both the distractor and the target were grouped together to form a single object. Similar results have been reported by Baylis and Driver (1992), Driver and Baylis (1989), and Harms and Bundesen (1983; but see also Berry & Klein, 1993;Kramer, Tham, & Yeh, 1991). The purpose of Experiment 4A was to investigate how attention might be distributed within the boundaries of a single object.…”
Section: Experiments 4asupporting
confidence: 64%
“…They demonstrated that the interference created by a distracting item on the processing of a target was increased if both the distractor and the target were grouped together to form a single object. Similar results have been reported by Baylis and Driver (1992), Driver and Baylis (1989), and Harms and Bundesen (1983; but see also Berry & Klein, 1993;Kramer, Tham, & Yeh, 1991). The purpose of Experiment 4A was to investigate how attention might be distributed within the boundaries of a single object.…”
Section: Experiments 4asupporting
confidence: 64%
“…The response compatibility effect is also influenced by Gestalt grouping principles that determine whether the target and distractors are seen as part of the same or different perceptual groups (or objects). Facilitation and interference are stronger when the target and distractors are part of the same group than when they are part of different groups (Baylis & Driver, 1992;Driver & Baylis, 1989;Harms & Bundesen, 1983;Kramer & Jacobson, 1991; also see Kahneman & Henik, 1981). This is interpreted as strong evidence for object-based attention: Object-based theorists argue that attention selects all of the properties of the selected object, relevant and irrelevant.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…An important direction for future research is to extend CODE and CTVA to deal with other grouping principles. Grouping by similarity is a good candidate for the first step in that direction because it is well studied perceptually (e.g., Beck, Prazdny, & Rosenfeld, 1983;Bergen, 1991 ) and it has powerful effects on attention (e.g., Baylis & Driver, 1992;Duncan & Humphreys, 1989;Harms & Bundesen, 1983;Humphreys & Miiller, 1993;Ivry & Prinzmetal, 1991;Wolfe, 1994). The mechanisms for dealing with similarity effects may already be present in CTVA.…”
Section: Proximity and Grouping Effects In Partial Report Several In-mentioning
confidence: 99%
“…Eriksen and Eriksen (1974) showed that, for two response sets of letters (H and K vs. S and C), irrelevant flankers from the wrong set interfered with making the response. This seems to be an attentional-selection problem, because presenting the flankers in a different color reduced the interference (Harms & Bundesen, 1983). Hatta, Hatae, and Kirsner (1984) contrasted English monolinguals to English-Japanese bilinguals in identifying English letters, and found that flanker characters from either language interfered for the bilinguals, but not for the monolinguals.…”
Section: Other Analogs Of the Stroop Taskmentioning
confidence: 99%